CONSUMER MOTIVATION FOR ORGANIC FOOD CONSUMPTION - Ergönül, Bülent; Ergönül, Pelin Günç (Emirates Journal of Food and Agriculture, 2015)
This paper presents the results from a Turkish survey study on perceptions, knowledge and behaviors of consumers towards organic foods. In order to provide information related to consumer motivation in purchasing organic products, 300 respondents were interviewed using face-to-face approach by adopting a survey. The results of these interviews are obtained, and also social and demographical attributes of the respondents were reported. Since organic products are perceived as difficult to find and expensive; most of the respondents judge them negatively. Data obtained from the survey showed that differences exist between groups of consumers with respect to their experience in consuming organic products and the extent of available information on these food products.